Phytoplankton diversity in three lakes of South Ural, Russia - ANASTASIYA M. KOSTRYUKOVA; TATYANA G. KRUPNOVA; IRINA V. MASHKOVA; SVETLANA V. GAVRILKINA; NIKITA O. EGOROV (Society for Indonesian Biodiversity, 2018)
Kostryukova AM, Krupnova TG, Mashkova IV, Gavrilkina SV, Nikita O. Egorov NO. 2018. Phytoplankton diversity in three lakes of South Ural, Russia. Biodiversitas 19: 1459-1467. Preservation of water ecosystems in their natural state is of great significance. Phytoplankton is one of the biotic indicators of the lake trophic status and ecological state. This study deals with phytoplankton diversity of three lakes of South Ural, Russia. The studied lakes represented different trophic states: Lake Savelkul was oligo-mesotrophic, Lake Ilmenskoe was mesotrophic and Lake Argayash was eutrophic. The species composition of common phytoplankton was recorded in June-July months during 2015 and 2016. The Cyanophyta (blue-green algae) species were dominant in Lake Ilmenskoe(42-64%) and Lake Argayash(55-70%). The Bacillariophyta (diatom algae) species were dominant in the Lake Savelkul(40-66 %). The most common diversity indices namely the Shannon Index, Simpson Index and Margalef Index were determined and the data was also analysed using graphs. The graphs were constructed by the similarity calculating method on the basis of the Sorensen-Czekanowski coefficient. Diversity indices confirm the higher species richness of the microalgal community of Lake Ilmenskoe, classified as mesotrophic. It was shown that the lakes have sufficiently high biodiversity and high ecosystem resilience. Further, statistical analysis (CCA) revealed that orthophosphate-phosphorus, nitrite-nitrogen and pH were the most significant environmental factors influencing phytoplankton community of the lakes studied.